Ethical Leadership Anomaly On Organizational Commitment In The Indonesian FDA - Dwi Rini Alkatya; Mochamad Soelton; Astrid Puspaningrum; Mohammed Hokroh; Harefan Arief (Universitas Mercu Buana, 2020)
This study aims to determine the influence of Ethical Leadership on Job Satisfaction, Ethical Climate and Organizational Commitment at staff at the Drug Registration Directorate of the Indonesian Food and Drug Authority (Indonesian FDA). Data collection techniques are done by distributing questionnaires using ordinal scales. This research was conducted on 70 respondents by using quantitative descriptive approach and hypothesis testing. The collected data is then analyzed using the technique analysis Structural Equation Modeling (SEM) through SmartPLS (Partial Least Square) software. The results of this study show that Ethical Leadership positively and significantly influence on Ethical Climate, Job Satisfaction and Organizational Commitment at the Drug Registration Directorate of the Indonesian Food and Drug Authority (Indonesian FDA).